Effector diversification contributes to Xanthomonas oryzae pv. oryzae phenotypic adaptation in a semi-isolated environment - Quibod, Ian Lorenzo; Perez-Quintero, Alvaro; Booher, Nicholas J.; Dossa, Gerbert S.; Grande, Genelou; Szurek, Boris; Vera Cruz, Casiana; Bogdanove, Adam J.; Oliva, Ricardo (Springer, 2016)
Understanding the processes that shaped contemporary pathogen populations in agricultural landscapes is quite important to define appropriate management strategies and to support crop improvement efforts. Here, we took advantage of an historical record to examine the adaptation pathway of the rice pathogen Xanthomonas oryzae pv. oryzae (Xoo) in a semi-isolated environment represented in the Philippine archipelago. By comparing genomes of key Xoo groups we showed that modern populations derived from three Asian lineages. We also showed that diversification of virulence factors occurred within each lineage, most likely driven by host adaptation, and it was essential to shape contemporary pathogen races. This finding is particularly important because it expands our understanding of pathogen adaptation to modern agriculture.